A g-C3N4/nanocarbon/ZnIn2S4 nanocomposite: an artificial Z-scheme visible-light photocatalytic system using nanocarbon as the electron mediator. Issue 96 (12th October 2015) - Shi, Fenfen; Chen, Linlin; Chen, Min; Jiang, Deli
Abstract : Nanocarbon could be used as an electron mediator to construct a Z-scheme photocatalytic system with enhanced charge separation efficiency. Abstract : A g-C3 N4 /nanocarbon/ZnIn2 S4 (CN/C/ZIS) nanocomposite with enhanced photocatalytic H2 production performance has been successfully synthesized. Based on the experimental results, for the first time, it has been demonstrated that nanocarbon could be integrated into a Z-scheme photocatalytic system and acted as an excellent solid electron mediator.